VOA Learning English: Enhancing Listening Proficiency in the Vocational Classroom - Niskarlina, Niskarlina; Usman, Usman; Bahnar, Siti Hardiyanti (Universitas Muhammadiyah Barru, 2025)
This study investigated the effectiveness of using the VOA Learning English website as a digital learning tool to enhance the English listening proficiency of X-year students at SMK Negeri 1 Barru. By comparing the performance of students who used the VOA Learning English website with those who rely on traditional methods, A quasi-experimental design with a pre-test and post-test was employed to evaluate the effectiveness of the VOA Learning English website in enhancing the English listening skills of X-year students at SMK Negeri 1 Barru. The study demonstrated that the use of VOA Learning English significantly enhanced students'' listening skills. The experimental group's post-test scores increased from an average of 54.20 to 86.70, while the control group's scores showed a less significant improvement. The significant improvement observed in the experimental group, as compared to the control group, highlights the potential of digital learning tools in transforming language education.